Novel Endocranial Data on the Early Therocephalian Lycosuchus vanderrieti Underpin High Character Variability in Early Theriodont Evolution - Pusch, Luisa C.; Ponstein, Jasper; Kammerer, Christian F.; Fröbisch, Jörg (Frontiers in Ecology and Evolution, 2020)
Therocephalia is one of the major therapsid clades and ranges from the middle Permian to Middle Triassic. The earliest therocephalians were large-bodied predators whose fossils are common in middle Permian rocks of South Africa, but have received little study. Here we present a redescription of the skull of the early therocephalian Lycosuchus based on a specimen from the middle Permian Tapinocephalus Assemblage Zone of the South African Karoo Basin. By using a computed tomographic (CT) reconstruction of this specimen, we describe for the first time several endocranial characters of this taxon including a highly ramified maxillary canal and the inner ear, which is characterized by a lengthened lateral semicircular canal, a feature previously only known from the anomodont Kawingasaurus among non-mammalian therapsids, and the presence of a cochlear recess, so far only known within Therocephalia from the highly specialized Triassic taxon Microgomphodon. We also provide new insights into patterns of tooth replacement in lycosuchids, which have proven controversial for this taxon. Craniodental characters generally support the placement of Lycosuchus as the most basal taxon in therocephalian phylogeny. The morphology of the maxillary canal and inner ear reveal a mosaic of features indicating a complex history of character acquisition and loss in Therocephalia, comparable to that of cynodonts.